The city school mathematical development workbook nursery term 2 (The City School Albakio International Lahore, 2016)
The Mathematical Development Workbook for nursery students at The City School is tailored to support young learners in building essential math skills during Term 2. This workbook emphasizes key concepts such as number recognition, basic operations, patterns, and measurement through engaging activities and colorful illustrations. Designed to stimulate curiosity and promote critical thinking, the workbook encourages children to explore mathematical ideas in a fun and interactive manner. By providing a strong foundation in early mathematics, it prepares students for future academic challenges and fosters a lifelong love for learning in the subject.